2020
DOI: 10.1155/2020/9752925
|View full text |Cite
|
Sign up to set email alerts
|

Does the Level of Confidence Exhibited by Dental Students Predict the Outcome of Complete Denture Therapy?

Abstract: Purpose/Objectives. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The multiple clinical and laboratory procedure involved in the fabrication and the multiple visits of the patient, makes the prosthetic replacement procedures tiring for both students and patients. A flaw in any laboratory procedure or lack of clinical skills can lead to improper fabrication of a denture hence causing patient dissatisfaction 23 . This finding was not enforced by other studies which could be due to the difference in curriculum and clinical requirements in other countries.…”
Section: Discussionmentioning
confidence: 94%
“…The multiple clinical and laboratory procedure involved in the fabrication and the multiple visits of the patient, makes the prosthetic replacement procedures tiring for both students and patients. A flaw in any laboratory procedure or lack of clinical skills can lead to improper fabrication of a denture hence causing patient dissatisfaction 23 . This finding was not enforced by other studies which could be due to the difference in curriculum and clinical requirements in other countries.…”
Section: Discussionmentioning
confidence: 94%
“…We found that students who felt more prepared had more confidence in their abilities, and felt they were ready to treat patients at an earlier time frame than their classmates. This is an important finding regarding curriculum development because even though clinical confidence and competency do not necessarily correlate, increasing self confidence in "clinical activities are considered an essential element in teaching dentistry [10]". Another study found that "complex procedures that were least practiced scored the lowest in overall mean (student) confidence" [11].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they do not always feel confident when providing treatment to patients, which might subject them to high levels of stress. [ 7 8 9 ] It is important to assess students’ stress levels in different conditions as high-stress can lower levels of academic commitment as well as impair students’ performance. [ 10 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patient cooperation and satisfaction plays a fundamental role in the success of the procedure. [ 8 ] Dental students often face a lot of difficulties dealing with edentulous cases and feel the burden to face the challenges of each clinical step involved. [ 12 13 ] As students’ progress in their training level, their confidence increases and stress levels during clinical procedures are expected to be minimized.…”
Section: Introductionmentioning
confidence: 99%